PENERAPAN METODE PICTURE AND PICTURE UNTUK MENINGKATKAN KEMANDIRIAN ANAK USIA DINI DI RA MUSLIMAT NU KALILEMBU KARANGDADAP PEKALONGAN - Muyanadifa, Siti; Munawaroh, Hidayatu; Faisal, Vava Imam Agus (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2019)
The low independence of early childhood in group B RA Muslimat NU Kalilembu Karangdadap Pekalongan. The objectives of this study are 1) To determine the application of the picture and picture method to increase the independence of early childhood in RA Muslimat NU Kalilembu Karangdadap Pekalongan. 2) To find out the increase in independence using the picture and picture method to increase the independence of early childhood in Ra Muslimat Nu Kalilembu Karangdadap Pekalongan. 3) To find out the Supporting and Inhibiting Factors using the picture and picture method to increase the independence of early childhood at RA Muslimat NU Kalilembu Karangdadap Pekalongan. The research method is carried out with quantitative research methods, field research, and experimental research. The subjects of this study were the children of group B in this study were students of groups A and B of RA Muslimat NU Kalilembu Karangdadap Pekalongan, totaling 71 children. Data collection techniques through interviews, observation and documentation. Data analysis used the one sample Kolmogrov-Smirnov test statistic. The results showed an increase in: 1) The application of the picture and picture method in the experimental group was that the teacher conveyed an understanding to the children about the picture and picture method in a simple way. Many learning activities involve children to be active by explaining about the use of pictures and what kinds of things are in the pictures and working on them without the help of other people, both teachers, parents, and other friends. Because the purpose of applying the picture and picture method is to determine the increase in the independence of early childhood. 2) The results of increasing independence using the application of the picture and picture method in the experimental group obtained the highest score of 15 and the lowest score of 11 with a score of 13.58. While the control group obtained the highest score of 14 and the lowest score of 9 with an average score of 10.75 which was included in the medium category, because the results of the N-Gain Score test were 0.592 with an interpretation of the effectiveness of the experimental group of 59.2% which was included in the quite effective category. . 3) There is a difference in the increase in independence. It is proven from the results of the t-test that t_count is 3.97, then the t_count is compared with t_table with an error rate of 1% of = 2.819, so that t_count > t_table = Ho is accepted. And it turns out that the results of this study obtained t_count > t_table, then Ha is accepted.